Implementasi Nilai Spiritual pada Lembaga Keuangan Syariah Perspektif Maqāṣid Asy-Syarīʿah - Istifadhoh, Nurul (SAUJANA : Jurnal Perbankan Syariah dan Ekonomi Syariah, 2025)
The spiritual value is a comprehensive, integrated and unified plan in the field of marketing, which provides guidelines regarding the activities to be carried out in order to achieve the marketing objectives of each company. In achieving company goals, there are two approaches, namely the material approach and the spiritual approach. The material approach is associated with real conditions in the field, while the spiritual approach is related to one's relationship with God Almighty. Spiritual value is a process of spiritual approach that aims to have a higher quality of life and can provide benefits to others around him. This article uses a descriptive qualitative research methodology. The results of the presentation of this article, namely 1) spiritual value which is included in the marketing strategy has a considerable influence on life, especially the family economy, apart from the pleasure of Allah SWT, it also invites members to participate and practice the contents of spiritual value. 2) The maqāṣid asy-syarīʿah perspective, the sharia marketing strategy carried out by KSPPS-MUI East Java has fulfilled basic needs according to Al-Ghozali including ḥifẓ al-dīn (maintaining religion), ḥifẓ an-nafs (preserving the soul), ḥifẓ al-' aql (maintaining the mind), ḥifẓ māl (maintaining wealth), and ḥifẓ al-irdl (maintaining honor). A marketing strategy that must have a positive influence on the beneficiaries. The implementation of spiritual value in the marketing strategy is carried out as a counterweight to the company's performance in obtaining convenience or success and being able to provide benefits to the community.